Dental wear in evolutionary and biocultural contexts - Schmidt, Christopher W.; Watson, James T. (Academic Press, an imprint of Elsevier, 2020)
520 "Dental Wear in Evolutionary and Biocultural Contexts provides a single source for disseminating the current state-of-the-art research regarding dental wear across a variety of hominoid species under a number of temporal and spatial contexts. The volume begins with a brief introductory chapter addressing the general history, understandings and approaches to the study of dental wear. Remaining chapters cover dental macrowear and dental microwear. Students and professionals in anthropology, specifically paleoanthropologists, bioarcheologists, archaeologists, and primatologists will find this book to be a valuable resource. In addition, it is a helpful guide for dentists and other dental professionals interested in dental function."--